THE URGENCY OF DRUG ABUSE PREVENTION IN MAINTAINING SOCIAL SECURITY STABILITY FROM THE PERSPECTIVE OF THE PROPHETIC HADITH: (A Thematic Study of Selected Hadiths from al-Kutub al-Sittah Using a Contextual Commentary Approach) - Ariangga Ramadhansyah; Budi Ichwayudi; Fairuz Zakirah (Al-Majaalis : Jurnal Dirasat Islamiyah, 2026)
This study analyzes the urgency of drug abuse prevention in maintaining social security stability from the perspective of the Prophet's Hadith. Conventional legalistic and biomedical approaches, while necessary, have proven insufficient to address the moral and social dimensions of the phenomenon, leaving a significant gap in normative-religious analyses grounded directly in the prophetic tradition. To fill this gap, the present study employs a qualitative library-research design with descriptive analysis of secondary data, applying Syarḥ al-Ḥadīth al-Siyāqī (Contextual Hadith Commentary) as articulated by Yūsuf al-Qaraḍāwī integrating textual, historical, and contemporary dimensions to five selected hadiths from al-Kutub al-Sittah. The findings demonstrate that these five hadiths jointly articulate a comprehensive prevention paradigm in which drug abuse constitutes a tangible manifestation of ḍarar threatening the foundations of social life. The prohibition of muskir wa mufattir grounds the protection of intellect; lā ḍarar wa lā ḍirār establishes a universal ethical prohibition against self- and social destruction; the hadith on yu'manu sharruh articulates social security as relational morality; the prohibition of self-destruction frames drug abuse as intihār baṭīʾ (slow suicide); and kullukum rāʿin distributes preventive accountability across every social stratum. Together, these hadiths operationalize the maqāṣid of ḥifẓ al-nafs, al-ʿaql, and al-nasl. Practically, the study proposes a prophetic-centered prevention model integrating value-based education, community-based rehabilitation, and multi-sectoral collaboration, complementing empirical prevention frameworks such as those of BNN (the Indonesian National Narcotics Board) and UNODC.